Magi. 9 : The labyrinth of magic. - Otaka, Shinobu (Viz Media, 2014)
"With peace restored in Balbadd, Aladdin and his friends have begun training in Sindria, the land of King sinbad. With the rise of Al-Thamen, an organization dedicated to spreading evil around the world, there is much to do. While Alibaba works to repair the Sword of Amon, visitors from the Kou Empire arrive with an interesting proposal. Then King Sinbad assigns a weighty task--they must enter Dungeon No. 61: Zagan..."--page [4] of cover.